TRAINING AND PERFORMANCE OF EARLY CHILDHOOD TEACHERS IN TIMES OF PANDEMICS: a CRITICAL-DIALECTIC ANALYSIS - Nakamura, Sueli Rosa; Bernardes de Arruda, Viviane Aparecida; Ferreira Barros, Marta Silene [UNESP]; Santos, Camila Crude dos (Univ Estadual Paulista-unesp, Fac Ciencias Letras Assis, 2022)
The discussions on teacher training and work have been expanded through the emergence of the Sars-Cov 2 virus, generator of the pandemic state of COVID-19, with the following questions: How is the training of Early Childhood Education teachers taking place in this pandemic context and how is it impacting the teaching performance? Thus, the general objective is to analyze the continuing education of teachers and its implications in Early Childhood Education. The present study was based on discussions and analyses that took place in the Discipline Education, human formation and praxis: implications of Marxism, Historical-Cultural Theory and Historical-Critical Pedagogy for School Education linked to the Post-Graduate Program in Education at the Londrina State University. The research is bibliographic with research and critical-dialectical analysis, with authors who deal with this perspective, which involves the Historical-Cultural Theory and the Historical-Critical Pedagogy, whose aim is to contribute in the new thinking the formation and action of the teacher of Early Childhood Education.
Keywords: Education; Early childhood education; Training and performance of teachers; COVID-19